2019
DOI: 10.1111/jdv.15847
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in the pathway to an optimal standard of care of hidradenitis suppurativa: the Italian Ultrasound Working Group experience

Abstract: Background Ultrasound (US) is a real‐time non‐invasive technique that has been demonstrated to support an early diagnosis and a more precise assessment of hidradenitis suppurativa (HS). Objectives To compare the clinical and US evaluation of a series of HS patients. Methods 434 HS patients (259 F, 175 M; mean age 33.82 ±13.31 years) observed across 19 Italian dermatology centres [members of the Italian Ultrasound Working Group (IUWG)] were enrolled in a retrospective study. Clinical staging was obtained by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…All included participants applied topical 15% resorcinol (incorporated in an oil/water cream as galenic product) once daily for 12 weeks in inflammatory HS lesions, including subcutaneous nodules, abscesses and sinus tracts. All patients were examined clinically and with ultrasonography at baseline, and at 4 and 12 weeks 4 . Clinical response [according to the Hidradenitis Suppurativa Clinical Response (HiSCR) measure] was achieved in 32 (52%) and 52 (85%) patients after 4 and 12 weeks, respectively ( P < 0·001).…”
Section: Clinical Hs Score Week T0 T4 T12mentioning
confidence: 99%
“…All included participants applied topical 15% resorcinol (incorporated in an oil/water cream as galenic product) once daily for 12 weeks in inflammatory HS lesions, including subcutaneous nodules, abscesses and sinus tracts. All patients were examined clinically and with ultrasonography at baseline, and at 4 and 12 weeks 4 . Clinical response [according to the Hidradenitis Suppurativa Clinical Response (HiSCR) measure] was achieved in 32 (52%) and 52 (85%) patients after 4 and 12 weeks, respectively ( P < 0·001).…”
Section: Clinical Hs Score Week T0 T4 T12mentioning
confidence: 99%
“…Lesions were categorized according to their sonographic morphology, and power Doppler (PD)-US criteria were assessed for diagnosing HS. [12][13][14][15] All sonographic examinations were performed by dermatologists experienced with HS who had completed the same training. In addition, identical equipment (MyLab TM One; Esaote, Genoa, Italy) with a 10-18 MHz linear transducer was used in both centres.…”
Section: Ultrasonographymentioning
confidence: 99%
“…It has already been demonstrated that VEGF production is strongly expressed in the keratinocytes overlying keloids 13 . Furthermore, in vitro studies have shown that it is expressed at higher levels in keloid‐derived fibroblasts than in normal skin 9,14 .…”
Section: Discussionmentioning
confidence: 99%